1994
DOI: 10.1016/0014-5793(94)80625-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the number of detergent molecules associated with the reaction center protein isolated from the photosynthetic bacterium Rhodopseudomonas viridis

Abstract: Detergent-free reaction center (RC) proteins from the photosynthetic bacterium Rhodopseudomonas viridis were obtained using Bio-Beads SM-2. With these RCs, the amount of detergent molecules associated with the protein was measured by determining the detergent concentration at which re-solubilization occurred as a function of the RC concentration. For N, N-dimethyl dodecylamine-N-oxide (LDAO), Triton X-100 and j?-octylglucoside 260 + 30,105 + 10 and 360 f 100 detergent molecules were necessary to dissolve the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…After minimization, the protein complex was embedded into a micelle that was composed of LDAO detergent molecules. Following the estimates of Gast et al 33 , 260 detergent molecules were used to solvate the TM portion of the protein. After insertion, around 187 Na + and 188 Cl − ions were added to the water phase to create a 0.2 M salt solution.…”
Section: Methodsmentioning
confidence: 99%
“…After minimization, the protein complex was embedded into a micelle that was composed of LDAO detergent molecules. Following the estimates of Gast et al 33 , 260 detergent molecules were used to solvate the TM portion of the protein. After insertion, around 187 Na + and 188 Cl − ions were added to the water phase to create a 0.2 M salt solution.…”
Section: Methodsmentioning
confidence: 99%
“…RC from R. sphaeroidees R26 were isolated as described in [ll]; they contained more than 90% QH acceptor. LDAO detergent was removed according to a method described earlier [9]. Briefly, the amount of detergent necessary to resolubilize a certain amount of detergent-free RC was determined by measuring the light scattering at 500 nm.…”
mentioning
confidence: 99%
“…20, 30, 40 10. 20, 30 (20) 4.5 Roth et al (1989) studied the size of the detergent ring surrounding this reaction centre in its crystallized form and the LDAO/reaction centre (RC) ratio value was found to be 110, a value more than two times lower than the value of 260 needed for the RC's solubilization (Gast et al, 1994). In work carried out on the structure of the detergent phase in the Rhodohacter sphaeroides (strain Y) reaction centre crystals (Roth et al, 1991) it was reported that /3-octylglucoside formed a beltshaped micelle around the hydrophobic 'waist' of the complex with interconnections between belts via micellar bridges.…”
Section: Introductionmentioning
confidence: 99%